2016
DOI: 10.1099/mgen.0.000060
|View full text |Cite
|
Sign up to set email alerts
|

Declaring a tuberculosis outbreak over with genomic epidemiology

Abstract: We report an updated method for inferring the time at which an infectious disease was transmitted between persons from a time-labelled pathogen genome phylogeny. We applied the method to 48 Mycobacterium tuberculosis genomes as part of a real-time public health outbreak investigation, demonstrating that although active tuberculosis (TB) cases were diagnosed through 2013, no transmission events took place beyond mid-2012. Subsequent cases were the result of progression from latent TB infection to active disease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…With time of exposure to an active TB case pinpointed within a two week period, and sometimes to a single day, Poulsen determined that these clinical features accompany TST conversion within 6 weeks of exposure (14,34,44). While these clinical features of initial M.tb infection are transient and not specific to M.tb infection, a method to determine that a person is currently in the first 1-2 years post initial infection would have great prognostic value for nearfuture TB disease and could allow real-time geospatial mapping of recent TB transmission in communities (14,15,17,(34)(35)(36)(37). In our proof of concept analysis, we sought to determine whether it is possible to develop an RNA-based blood test to detect recent exposure or infection with M.tb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With time of exposure to an active TB case pinpointed within a two week period, and sometimes to a single day, Poulsen determined that these clinical features accompany TST conversion within 6 weeks of exposure (14,34,44). While these clinical features of initial M.tb infection are transient and not specific to M.tb infection, a method to determine that a person is currently in the first 1-2 years post initial infection would have great prognostic value for nearfuture TB disease and could allow real-time geospatial mapping of recent TB transmission in communities (14,15,17,(34)(35)(36)(37). In our proof of concept analysis, we sought to determine whether it is possible to develop an RNA-based blood test to detect recent exposure or infection with M.tb.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether our findings in mice and cynomolgus macaques could translate to humans, several points are important to consider. While a recent study in the United States and Canada showed that recent contacts of active TB cases are at highest risk of TB disease in the first 1-3 months after the diagnosis of the TB index case, studies in other countries and other time periods show that the highest risk is in the first 1-2 years, with most cases accruing more than 2-3 months after a documented exposure (14,17,(34)(35)(36)(37). A recent vaccine study in rhesus macaques showed that BCG-induced immunity to M.tb delays IGRA conversion in a repeated limiting-dose M.tb challenge model (38).…”
Section: Blood Rna Expression Of 250 Genes Predicts Time Since Activementioning
confidence: 99%
“…Even on a wider 377 geographic scale, where comprehensive sampling of an outbreak cannot be guaranteed, 378 the approach demonstrated here can generate concrete recommendations for public 379 health authorities. Transmission-network reconstructions of a tuberculosis outbreak in disease, rather than active transmission, with the direct result that the outbreak was declared over, a conclusion that was reached solely by comparison of the rate of de 383 novo mutation between samples (Hatherell et al 2016). Adapting such a capacity to 384 malaria would have major implications for elimination efforts: malaria elimination within a 385 country is defined as zero incidence of indigenous cases (WHO 2016) and the ability to 386 distinguish a chain of transmission from repeated importations without recourse to a 387 multi-country dataset could be a key capacity for the WHO Global Malaria Program.…”
Section: Future 306mentioning
confidence: 99%
“…For a reportable disease like TB, with nearly exclusive human‐to‐human transmission, and in a well‐resourced, low‐incidence setting where culture is routinely used in diagnosis, this is often achievable. For example, in a recent British Columbia TB outbreak, we obtained Mtb DNA from 48 of 52 outbreak cases . For non‐notifiable diseases and/or those involving food‐ or water‐borne transmission or nonhuman hosts, the outbreak may be insufficiently represented by the available samples.…”
Section: Step 1: Look Before You Leapmentioning
confidence: 99%
“…For example, in a recent British Columbia TB outbreak, 36 we obtained Mtb DNA from 48 of 52 outbreak cases. 37 For nonnotifiable diseases and/or those involving food-or water-borne transmission or nonhuman hosts, the outbreak may be insufficiently represented by the available samples.…”
Section: Step 1: Look Before You Leapmentioning
confidence: 99%